Soil Micronutrient and Heavy Metal Status, Uptake and Yield of Soybean-Wheat Cropping Sequence as Influenced by One Time Controlled Application of Primary Treated Biomethanated Spentwash and Chemical Fertilizers - A.N. Deshpande, B.M. Kamble and (Journal of the Indian Society of Soil Science, 2015)
The field experiment on effect of one time application of primary treated biomethanated spentwash (PBSW) and chemical fertilizers on DTPA micronutrients, heavy metal status, uptake and yield of soybean–wheat cropping sequence on Inceptisol was conducted at Post Graduate Research Farm, Mahatma Phule Agricultural University, Rahuri, Maharashtra. The experiment was laid out in RBD with five treatments viz., recommended dose (RD)-NPK, 100% RD of nitrogen (N) through PBSW with and without phosphorus (P) chemical fertilizer, 50 and 25% RD of N through PBSW + remaining N and P through chemical fertilizers with four replications. The results revealed that the DTPA micronutrient availability (Fe, Zn, Mn and Cu) was increased due to increased in quantity of PBSW application in all soil depths and it was higher and above the critical limit in all the three soil depths during two year study as compared to RD-NPK. The DTPA-Zn content was always below critical limit (0.6 mg kg-1) during the period of experiment in all the soil depths of RD-NPK. However, it was below the critical limit in all the three soil depths with 50 and 25% RD of N through PBSW + remaining N and P through chemical fertilizers at wheat harvest 2010-11. The DTPA heavy metal (Ni, Cd and Pb) status increased in all the PBSW treatments in both the years of experiment and these values were below the critical /permissible limit in soil. The significantly highest total Fe, Zn, Mn and Cu uptake by soybean-wheat cropping sequence was observed in 25% recommended N through PBSW + remaining N and P through chemical fertilizers, however it was at par with RD-NPK for total Fe and Mn uptake. The treatment 25% RD of N through PBSW + remaining N and P through chemical fertilizers was recorded the highest pooled means grain and straw yields of soybean over the rest of treatments. The RD-NPK treatment recorded the highest pooled grain and straw yields of wheat, however it was at par with 25% RD of N through PBSW + remaining N and P through chemical fertilizers during the year 2010-11 and in pooled means.